2013
DOI: 10.1002/pssr.201307029
|View full text |Cite
|
Sign up to set email alerts
|

Au–Ge bonding on a uniformly Au‐covered Ge(001) surface

Abstract: The structure and electronic properties of the system resulted by epitaxial growth of a single atomic Au layer on a heated Ge(001) surface featured by (2 × 1) reconstruction are studied. The deposition at ∼750 K results in a well‐ordered Au surface featured by ripples separated by four times the theoretical distance between two neighboring Au atoms. As revealed by valence‐band photoemission studies, the Au/Ge(001) system has metallic character. Correlating X‐ray photoelectron spectroscopy results with first‐pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Similar findings may be inferred also from the Ge 2p spectra. Therefore, although the LEED pattern is similar, it may happen that the orientation of the dimers and their charge state is modified in the case of MnGe(001) with respect to the case of clean Ge(001), as was evidenced also for Au/Ge(001) [26,27]. This result is in line with the STM observations from Figure 2b, namely the different interatomic distance obtained for the surface dimers.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Similar findings may be inferred also from the Ge 2p spectra. Therefore, although the LEED pattern is similar, it may happen that the orientation of the dimers and their charge state is modified in the case of MnGe(001) with respect to the case of clean Ge(001), as was evidenced also for Au/Ge(001) [26,27]. This result is in line with the STM observations from Figure 2b, namely the different interatomic distance obtained for the surface dimers.…”
Section: Resultssupporting
confidence: 84%
“…Additional proof is as follows: when Au is deposited on a similar Ge(001) wafer as used in the actual experiments at relatively low temperature, a band bending of the Ge 3d “bulk” component is obtained by ~0.15 eV towards lower binding energies [26], as expected from the difference of workfunctions between Au (5.1–5.3 eV) and Ge (5.0 eV) [50]. When Au is deposited at elevated temperature (750 K), the band bending reverses its sign: it yields about 0.1 eV towards higher binding energies [27], close to the actual case. The origin of this reversed band bending (irrespective of the workfunction of the metal used) suggests the presence of defects introduced by the metal under the Ge(001) surface, which act as shallow acceptors [51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A final observation addresses the stability of the interface formation as deduced from DFT calculations . Au lattice constant aAu=4.078 Å is close to that of BTO strained at the in‐plane STO lattice constant, aSTO=3.905 Å. Consequently, one would expect that the epitaxy condition is rather easily fulfilled for Au growth.…”
mentioning
confidence: 72%
“…139,172,176,177 It was even shown that for 1 ML Au deposition replacing all surface Ge-dimers by Au-dimers leads to a very stable configuration, which agrees very well with the experimental observation of the formation of 3D Au islands under high deposition amounts. 172,178 It also explains why no β-terraces are observed for the Au-deposited systems.…”
Section: Simple Models For Au Nanowiresmentioning
confidence: 95%